Extracellular Vesicles in Bone Tumors: How to Seed in the Surroundings Molecular Information for Malignant Transformation and Progression - Cappariello, Alfredo; Rucci, Nadia (Frontiers in Oncology, 2021)
Bone is a very dynamic tissue hosting different cell types whose functions are regulated by a plethora of membrane-bound and soluble molecules. Intercellular communication was recently demonstrated to be also sustained by the exchange of extracellular vesicles (EVs). These are cell-derived nanosized structures shuttling biologically active molecules, such as nucleic acids and proteins. The bone microenvironment is a preferential site of primary and metastatic tumors, in which cancer cells find a fertile soil to “seed and blossom”. Nowadays, many oncogenic processes are recognized to be sustained by EVs. For example, EVs can directly fuel the vicious cycle in the bone/bone marrow microenvironment. EVs create a favourable environment for tumor growth by affecting osteoblasts, osteoclasts, osteocytes, adipocytes, leukocytes, and endothelial cells. At the same time other crucial tumor-mediated events, such as the premetastatic niche formation, tumor cell dormancy, as well as drug resistance, have been described to be fostered by tumor-derived EVs. In this review, we will discuss the main body of literature describing how the cancer cells use the EVs for their growth into the bone and for educating the bone microenvironment to host metastases.